Achieving polycrystalline diamond magnetic abrasive tools via double-stage gas atomization. (December 2022) - Gao, Yuewu; Zhao, Yugang; Zhao, Guoyong; Zhang, Guixiang; Zhang, Haiyun
Graphical abstract: Highlights: A novel method for preparing PCD magnetic abrasive powder (MAPs) was created using an atomization technique. The PCD abrasive's ideal cooling temperature on inhibiting its graphitization and the pressure of the first-stage atomizer on the dispersion of abrasive in the matrix were discovered. A dense layer of PCD abrasives with the original crystal structure was embedded on the surface of the matrix in the prepared MAPs and demonstrated good circularity. An end result roughness to cemented carbide of 85.2 nm was attained using PCD MAPs. Abstract: Although magnetic abrasive finishing (MAF) is an efficient surface finishing technique, its promotion and use in the precise polishing of high-hardness objects are constrained by the poor finishing performance and short service life of magnetic abrasive powders (MAPs). In this study, a double-stage atomization technique is employed to successfully manufacture MAPs with a polycrystalline diamond (PCD) as an abrasive phase. Analysis was performed on the graphitization of PCD abrasive and the circularity of the created MAPs as a result of cooling temperature. Therefore, the pressure ranges of the first-stage atomizer are suggested based on the theoretically designed kinetic model of PCD abrasives' penetration behavior into liquid metal. As revealed in the preparation experiment findings, PCD abrasives with their original crystal structure were deeply embedded on the surface of a spherical iron matrix. The generated PCD MAPs with smaller particle sizes exhibited better soft magnetic characteristics due to the atomization process' quick cooling. The MAF results implied that PCD MAPs curtailed the roughness of cemented carbide from 302 nm to 85.2 nm, and their service life exceeds 60 min. The findings of this research can provide technical assistance for the creation of high-performance PCD MAPs.